Keberhasilan Pelatihan Budidaya Cabai Secara Hidroponik Dutch Bucket Kepada Kelompok Wanita Tani Mekar Sari - Nur Hidayat; Daryono Daryono; Rusmini Rusmini; Faradilla Faradilla; M. Atta Bary (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mekar Sari Women Farmers Group (KWT) Sidomulyo Village, Anggana Subdistrict, Kutai Kartanegara Regency is a group of mothers who work in agriculture, by utilizing the yard land that is not too large, hydroponic chili cultivation is considered to provide a place for KWT mothers to carry out their activities. Through community service activities, by providing training in hydroponic chili cultivation using dutch buckets. The purpose of this training is to determine the success of hydroponic chili cultivation training, especially dutch buckets for Women Farmers Group mothers in Sidomulyo Village. The training includes Technology Demonstration, Focus Group Discussion and making dutch bucket hydroponics and hydroponic chili cultivation. Training participants filled out a questionnaire to determine the level of Effectiveness of Knowledge Change (EPP). Based on the results of the EPP analysis with a value of 69.83%, it is categorized as very effective. So that this activity is considered successful.